SEJARAH KERESIDENAN PALEMBANG - Kemas A.R. Panji; Sri Suriana (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2014)
Abstract:Since the abolition of the Sultanate of Palembang Darussalam in 1825 by the Dutch colonial government, the town changed its status becoming Resident region, led by a Resident. Pointing Dutch government or lift a man named J.L. van Sevenhoven as First Resident. Palembang residency divided into several Afdeeling except in the capital of Palembang. Afdeeling each headed by a Resident Assistant. Each Afdeeling consists of Onder Afdeeling headed by a controller. Each Onder Afdeeling there are clans, each headed by a Chief Marga (Pasirah). While the capital city of Palembang is divided into two, namely the District across Ilir District and District Seberang Ulu held by a Demat. Residency of Palembang, Jambi, Lampung and Bangka Belitung included in the Province of South Sumatra, is the fourth residency in the early days were in the area Administrative Sumatra (1 province) with capital of Medan, Sumatra then divided into 3 new Province namely: North Sumatra Province (It consists of Residency of Aceh, East Sumatra (Medan), and Tapanuli), Central Sumatra Province (It consist of Resident of West Sumatra (Bukit Tinggi), Riau, Jambi), South Sumatra Province (consisting of: Residency of Palembang, Bengkulu, Lampung and Bangka-Belitung). Post-Expansion into 3 provinces of Sumatra, Palembang Resident position changes its status to the Governor of South Sumatra. Keywords: Residency of Palembang, Resident, South Sumatra Province, Governor.